Peranan Sifat Fisikokimia Sorgum Dalam Diversifikasi Pangan Dan Industri Serta Prospek Pengembangannya - Suarni Suarni (Jurnal Penelitian dan Pengembangan Pertanian, 2016)
ABSTRACTSorghum utilization for foods and industries from semi-finished materials (milled grains, flour, starch) should be based on the character of physicochemical properties. This is supported by results of research that each sorghum variety has physicochemical properties and different functional bioactive compounds. This is a first step for selecting sorghum varieties appropriate with desired products. There are many technology innovations of industry and food products, including liquid sugar and bioethanol from sweet sorghum stem. To promote sorghum as prospective food and industry diversification materials, research support, science and technology, and policy are required. The availability of superior sorghum varieties supported by technological innovation of food processing industry makes it potential commodity to be developed.Keywords: Sorghum, physicochemical properties, food diversification, industryabstrakPemanfaatan sorgum untuk pangan dan industri dari bahan setengah jadi (sorgum sosoh, tepung, dan pati) sebaiknya berlandaskan pada karakter sifat fisikokimia. Hasil penelitian menunjukkan bahwa setiap varietas sorgum memiliki sifat fisikokimia dan komponen bioaktif fungsional yang berbeda. Informasi ini dapat menjadi pertimbangan awal dalam memilih varietas sorgum sesuai dengan produk yang diinginkan. Berbagai inovasi teknologi produk pangan dan industri berbasis sorgum, termasuk gula cair dan bioetanol dari batang sorgum manis telah dihasilkan. Untuk mempromosikan sorgum sebagai bahan diversifikasi pangan dan industri yang prospektif, diperlukan dukungan riset, iptek, dan kebijakan. Tersedianya varietas unggul sorgum, yang didukung dengan inovasi teknologi pengolahan pangan dan industri yang memadai, menjadikan komoditas ini potensial untuk dikembangkan.